(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Marshall Syndrome PFAPA (Periodic Fever, Aphthous Stomatitis, Pharyngitis, Adenitis) Syndrome is a chronic condition, typically starting 2-5 years old, in which fever occurs periodically (lasts for 3-7 days), accompanied by aphthous-like ulcers, pharyngitis and/or cervical adenitis. The patients have no clinical symptoms between episodes and it is required to exclude all other diseases before confirming the diagnosis. The dramatic response to treatment with steroid helps diagnosing PFAPA. We are presenting the case of an 8 years male patient, with the history of recurrent episodes of fever (onset at the age of two), oral ulcer and difficulty in deglutition who constantly received antibiotic therapy and or antifungal prescribed by different doctors. Clinically the patient was febrile, mildly pale, cervical lymphadenopathy, aphthous ulcers in the tongue with inflamed tonsils, covered with thick exudates and pharyngeal wall was inflamed and folliculated. There was just palpable liver. Laboratory investigations performed but it was without serological confirmation. Throat swab culture was negative. The child received steroid (Prednisolone) with favorable outcome. Subsequently, the patient presented with similar episodes of fever which disappeared within 24 hours of single dose of prednisolone. After Ranitidine (H2 blocker) prophylaxis the patient remains asymptomatic for about one and half years. With our best knowledge this is the first case report of Marshall Syndrome or PFAPA Syndrome in Bangladesh. J Bangladesh Coll Phys Surg 2016; 34(4): 222-224